PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA PENGADILAN AGAMA BEKASI KELAS 1A - Berliana Febrianti; Ni Nyoman Sawitri, Dovina Navanti, Hapzi Ali, Muhammad Asif Khan (BORJUIS: JURNAL OF ECONOMY, 2024)
Human Resources (HR) is the main component of an organization which is an active planner and actor in every organizational activity. There are many factors that influence employee performance, such as leadership style. Leadership style is a set of characteristics that leaders use to influence subordinates so that organizational goals are achieved or it can also be said that leadership style is a pattern of behavior and strategies that are liked and often applied by a leader. Organizational culture is also a factor that influences employee performance. Organizational culture is the collective beliefs, values, rituals and myths that determine the way people in an organization behave, and work motivation influences employee performance. Work motivation is the key of a successful organization to maintain continuity of work in the organization in a strong way and help to survive. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) Leadership style influences employee performance, 2) Organizational culture influences employee performance, 3) Work motivation influences employee performance.